Implementation of Article 12 of the UN Convention on the Rights of Persons with Disabilities in the Republic of Finland - Mikkola, Tuulikki (Routledge, 2025)
Finland is a democratic state governed by the rule of law, with the Constitution (731/1999, in Finnish: perustuslaki) giving every individual strong protection for human dignity, self-determination and integrity, in addition to other fundamental rights. The rule of law is based on legislation that protects fundamental and human rights and is applied in independent courts and authorities. Finland is committed to complying with international human rights treaties and EU provisions on fundamental rights.1
1 See the webpages of a Finnish government, https://valtioneuvosto.fi/en/marin/government-programme/safe-and-secure-finland-built-on-the-rule-of-law.
Models of Implementation of Article 12 of the Convention on the Rights of Persons with Disabilities (CRPD): Private and Criminal Law Aspects